Interobserver variability in organ delineation on radiotherapy treatment planning for nasopharyngeal carcinoma: A dosimetric and prognostic analysis - Chen, Meining; Peng, Yinglin; Chen, Ruotong; Xie, Qiuying; Chen, Dengyuan; Shi, Jinping; Huang, Rong; Zhang, Jun; Zhao, Chong; Chen, Li; Deng, Xiaowu; Liu, Yimei (Frontiers in Oncology, 2025)
Background and purposeThis study aimed to analyze the impact of interobserver variability (IOV) on clinical dosimetry and prognosis, specifically investigating the correlation between IOV and clinical prognosis in the context of intensity-modulated radiation therapy (IMRT) for nasopharyngeal carcinoma (NPC).Materials and methodsTwelve NPC patients who underwent IMRT were selected. Four radiotherapy physicians from two different-tier cancer centers independently delineated target volumes and organs at risk (OARs) for each patient. These delineations were compared against gold standard structures from a regional cancer center. The IOV among physicians and its effect on clinical and prognosis were analyzed. The relationships between the IOV, dosimetry, and prognosis were investigated using spearman’s correlation analysis.ResultsThe target volume and OARs delineation differed significantly among physicians. This variability led to reduced prescription dose coverage (PDC) of the planning target volume (PTV) and increased doses to OARs, impacting tumor control probability (TCP) and normal tissue complication probability (NTCP). Compared to standard delineations, all four physicians showed decreased TCPs (average decrease in ΔTCP >1%) and a significant increase in NTCPs of OARs. The relative volume difference (ΔV) of target volumes correlated strongly with ΔPDC (R=0.686) and ΔTCP (R=0.703). Moreover, in the validation set, ΔV also strongly correlated with ΔTCP (R = 0.778).ConclusionSubstantial IOV in delineating NPC target volumes and OARs for IMRT was observed. This variability affects plan optimization, dose distribution, and clinical prognosis. ΔV can serve as a risk predictor for assessing delineation variability in NPC radiotherapy treatment planning.